Perlindungan Hukum Bagi Seller di Aplikasi Shopee yang Akunnya Diblokir Sepihak oleh PT Shopee - Amalia Alya Azhari; Indah Parmitasari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Buying and selling through the Shopee application in practice has a problem, namely the seller's account is unilaterally blocked by Shopee, it is done without the seller's knowledge and there is no notification about the seller's error, which results in harming the seller. The formulation of the problem in this research is the first, how is the legal protection for sellers in the Shopee application whose accounts are unilaterally blocked by PT Shopee? Second, can the unilateral blocking action by PT Shopee against business actors (sellers) be said to be an act against the law? The research method is normative legal research, with a statutory approach, case approach and conceptual approach. The data used is secondary data obtained by literature studies and analyzed with qualitative descriptions. The results of the research findings are first, legal protection for sellers in the Shopee application whose accounts are unilaterally blocked by PT Shopee is with preventive legal protection, namely the regulation that the implementation of the agreement must be based on good faith, propriety, and caution. While the protection of repressive law with lawsuits against the law filed by business actors. Second, the unilateral blocking action by PT Shopee against the seller (seller) can be said as an act against the law, because it has fulfilled the elements of an act against the law like Article 1365 of the Civil Code, namely the existence of an act against the law, the existence of mistakes, the presence of causes and consequences between loss and actions, and the existence of losses.